2009
DOI: 10.1128/aac.01021-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity of a New Cephalosporin, Ceftaroline, and Determination of Quality Control Ranges for MIC Testing

Abstract: The spectrum of activity of ceftaroline was evaluated against 1,247 bacterial isolates representing 44 different species or phenotypic groups. For the majority of species, the activity of ceftaroline was comparable or superior to that of ceftriaxone. MIC and/or disk diffusion quality control ranges of ceftaroline were determined for five standard ATCC reference strains.Ceftaroline fosamil (formerly PPI-0903 , an N-phosphono prodrug cephalosporin, is a novel, parenteral, bactericidal, anti-methicillin-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 10 publications
(7 reference statements)
5
30
0
1
Order By: Relevance
“…Ceftaroline also retains its potency against coagulase-negative staphylococci with reduced susceptibility to linezolid, daptomycin, and vancomycin (32). The current study found Ͼ99% of isolates of MRSA, including both health care-associated and communityassociated isolates of MRSA, to be susceptible to ceftarolineavibactam and ceftaroline, similar to results reported by other investigators (5,(27)(28)(29). Isolates of MRSA collected by the CANWARD surveillance study in 2009 (2) demonstrated an MIC 90 (1 g/ml) identical to the one reported by the current study for isolates tested from 2010 to 2012.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Ceftaroline also retains its potency against coagulase-negative staphylococci with reduced susceptibility to linezolid, daptomycin, and vancomycin (32). The current study found Ͼ99% of isolates of MRSA, including both health care-associated and communityassociated isolates of MRSA, to be susceptible to ceftarolineavibactam and ceftaroline, similar to results reported by other investigators (5,(27)(28)(29). Isolates of MRSA collected by the CANWARD surveillance study in 2009 (2) demonstrated an MIC 90 (1 g/ml) identical to the one reported by the current study for isolates tested from 2010 to 2012.…”
Section: Discussionsupporting
confidence: 81%
“…If the ceftaroline FDA susceptibility breakpoint for Enterobacteriaceae (susceptible, Յ0.5 g/ml) was used for ceftarolineavibactam, the susceptibility rate was Ͼ99% (3,846/3,879 isolates) for all Enterobacteriaceae tested. Ceftaroline is known to be hydrolyzed by ESBL, AmpC, KPC, and metallo-␤-lactamases, and its in vitro activity is reflected by the prevalence of these enzymes in isolate collections (9,27,28,29). Isolates of Enterobacteriaceae collected by the CANWARD surveillance study in 2009 (2) demonstrated levels of susceptibility to ceftaroline similar to those reported in the current study from 2010 to 2012 (Table 1).…”
Section: Discussionsupporting
confidence: 65%
“…Ceftaroline demonstrated in vitro activity against all CA-MRSA isolates, regardless of their SCCmec type, with MICs ranging from 0.25 to 1 g/ml and with the MIC 90 being 1 g/ml. These findings are supported by those of earlier studies, in which the ceftaroline MICs ranged from 0.25 to 1 g/ml for CA-MRSA and from 0.12 to 2 g/ml for MRSA (1,6,10,14,15,20,21). Daptomycin nonsusceptibility among VISA isolates has been reported (11,17), potentially limiting the treatment options for patients infected with these pathogens.…”
supporting
confidence: 80%
“…After 50 serial subcultures, ceftaroline did not yield resistant clones and demonstrated MICs consistent with previously published reports against all strains of S. aureus, S. pneumoniae, S. pyogenes, M. catarrhalis, and K. pneumoniae tested (8,20,22,31,46,49,50,53,57). One of four H. influenzae strains tested (a quinolone-resistant isolate) produced a ceftaroline clone with increased MIC of 0.06 to 1 g/ml after 20 days of passaging.…”
Section: Discussionsupporting
confidence: 71%